CyanoBase: a large-scale update on its 20th anniversary. Issue Volume 45:Issue D1(2017) (28th November 2016) - Fujisawa, Takatomo; Narikawa, Rei; Maeda, Shin-ichi; Watanabe, Satoru; Kanesaki, Yu; Kobayashi, Koichi; Nomata, Jiro; Hanaoka, Mitsumasa; Watanabe, Mai; Ehira, Shigeki; Suzuki, Eiji; Awai, Koichiro; et al.
Abstract: The first ever cyanobacterial genome sequence was determined two decades ago and CyanoBase (http://genome.microbedb.jp/cyanobase ), the first database for cyanobacteria was simultaneously developed to allow this genomic information to be used more efficiently. Since then, CyanoBase has constantly been extended and has received several updates. Here, we describe a new large-scale update of the database, which coincides with its 20th anniversary. We have expanded the number of cyanobacterial genomic sequences from 39 to 376 species, which consists of 86 complete and 290 draft genomes. We have also optimized the user interface for large genomic data to include the use of semantic web technologies and JBrowse and have extended community-based reannotation resources through the re-annotation of Synechocystis sp. PCC 6803 by the cyanobacterial research community. These updates have markedly improved CyanoBase, providing cyanobacterial genome annotations as references for cyanobacterial research.